2010
DOI: 10.1080/19415250903454767
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a university lecturer in teacher education: expert school teachers reconstructing their pedagogy and identity

Abstract: This article contributes to understanding of the professional learning of expert school teachers when they are appointed as university-based teacher educators. In this case study of a single department a qualitative analysis is used to interpret the transcripts of sixteen semi-structured interviews with lecturers in teacher education within four years of their appointment to higher education roles. They experience tensions within the educational partnership and professional field about the value of abstract kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 20 publications
8
93
1
6
Order By: Relevance
“…Indeed, environmental and cultural factors within a university, for example, time constraints and teaching excellence focussed curricula are often cited as barriers rather than facilitators to improving scholarly publication outputs (Clughen and Connell, 2011). The transition into an academic role has been identified as challenging even for experienced scholars, with individuals doubting their credibility and competence (Boyd and Harris, 2010). This experience has been echoed by writers who fear being exposed as 'frauds', with feelings of perfectionism and shame towards their writing (Grant and Knowles, 2000) many academics and research students experience writing-related struggles (Caffarella and Barnett, 2000;Cameron et al, 2009) with reported concerns of having their inadequacies exposed in their published writing.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…Indeed, environmental and cultural factors within a university, for example, time constraints and teaching excellence focussed curricula are often cited as barriers rather than facilitators to improving scholarly publication outputs (Clughen and Connell, 2011). The transition into an academic role has been identified as challenging even for experienced scholars, with individuals doubting their credibility and competence (Boyd and Harris, 2010). This experience has been echoed by writers who fear being exposed as 'frauds', with feelings of perfectionism and shame towards their writing (Grant and Knowles, 2000) many academics and research students experience writing-related struggles (Caffarella and Barnett, 2000;Cameron et al, 2009) with reported concerns of having their inadequacies exposed in their published writing.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…A second theme that has been addressed is that of the professional development of teacher educators. There is now a growing body of knowledge about the induction of teacher educators in Europe (Van Velzen et al 2010) and in specific countries such as England (Boyd and Harris 2010) and Israel (Shagrir 2010). There is also an emerging body of knowledge on ways to increase the quality of teacher educators that has a focus on the learning of experienced professionals, such as learning in a community.…”
Section: Introductionmentioning
confidence: 99%
“…Although a full discussion of this issue is beyond the scope of the current article it is worth noting parallels here with other recent work with individuals new to teaching in higher education (Boyd and Harris 2010).…”
Section: Discussionmentioning
confidence: 75%